Zinc-bromine battery based on violuric acid ammonium modified electrolyte and preparation method of zinc-bromine battery

By using ammonium violacetate modified electrolyte in zinc-bromine batteries, the problem of bromine gas generation during the charge and discharge process of zinc-bromine batteries is solved, the discharge voltage and capacity of the battery are improved, the life is extended, and low-cost, high-efficiency batteries are realized. Performance new zinc-bromine battery.

CN119361859APending Publication Date: 2025-01-24DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411458553.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing zinc-bromide batteries produce bromine gas during charging and discharging, resulting in environmental pollution and corrosion of zinc electrodes. They have a short lifespan. The maximum capacity is generally around 1.5mAh/cm2, and the number of cycles does not exceed 200 times.

Method used

Using zinc bromate batteries based on ammonium ammonium ammonium ammonium ammonium migrate, reduce water molecular activity by high concentration of zinc bromide, add potassium hydroxide pH value, and use potassium bromate and ammonium ammonium ammonium to modify the electrolyte. Reduce the production of bromine gas, increase the discharge voltage and capacity of the battery, and extend the life of the battery.

Benefits of technology

The high discharge voltage and capacity of zinc bromo batteries are realized, the battery life is extended to 2,000 cycles, and costs and environmental pollution risks are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361859A_ABST
    Figure CN119361859A_ABST
Patent Text Reader

Abstract

The invention provides a zinc-bromine battery based on a violuric acid ammonium modified electrolyte and a preparation method of the zinc-bromine battery, and belongs to the field of batteries. According to the zinc-bromine battery, potassium hydroxide, potassium bromate and ammonium mureate are added into a high-concentration zinc bromide solution to serve as electrolyte, graphite paper serves as a positive electrode, and a zinc sheet serves as a negative electrode. According to the method, the ammonium mureate additive is added into the zinc bromide aqueous solution to form a complex with bromide ions, potassium bromate is used for inducing disproportionation reaction of the bromide ions, the capacity of the zinc-bromine battery can be improved, the service life of the zinc-bromine battery can be prolonged, a soft package battery can be manufactured, and a membrane-free and flow-free box-packed battery can also be manufactured. Compared with a zinc-bromine battery proposed in recent years, the graphite paper and the zinc sheet which are low in price and stable in performance are directly used as electrode materials, use of expensive materials and a complex process are avoided, the manufacturing cost of the battery is reduced, and harm of the battery materials to the environment is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and relates to a zinc-bromine battery based on a murexide-modified electrolyte and a preparation method thereof, and is a novel low-cost, high-discharge platform, long-life zinc-bromine battery and a preparation method thereof. Background Art

[0002] In recent years, lithium-ion batteries have occupied most of the energy storage market. However, due to the scarcity of lithium resources and the insecurity of lithium-ion batteries, people have been studying non-lithium-ion batteries, such as potassium ion, sodium ion, zinc ion, aluminum ion, chloride ion, fluoride ion and zinc-bromine batteries, and have made some progress. Among the many candidate products, aqueous zinc-bromine batteries have received considerable attention. Metallic zinc provides a high volumetric capacity density (5855mAh / cm 3 ), low redox potential (E = -0.76 V vs. standard hydrogen electrode (SHE)), and good stability in aqueous media. Bromine shows excellent electrochemical activity with high redox potential and capacity (1.07 V vs. SHE, 335 mAh / g).

[0003] At present, most of the research on zinc bromide batteries is focused on flow batteries. However, the composition of zinc-bromine flow batteries requires some expensive components, such as circulation pumps and reactors. Therefore, non-flow zinc bromide batteries can greatly reduce costs and simplify battery structure. Another problem with zinc-bromine battery systems is the generation and volatilization of bromine gas during charging and discharging, which not only poses a threat to the environment, but may also cause the Br-containing - The electrolyte converts Br2 into polybrominated Br n - (n=2x+1,x=1,2). However, due to the high solubility of polybrominated compounds, this also brings about the problem of polybrominated compound shuttling. This leads to low Coulombic efficiency and may cause corrosion of the zinc electrode. In addition, during the charge and discharge process, uneven zinc deposition may also occur on the zinc electrode, leading to dendrite growth and zinc dissolution into the electrolyte, reducing the life of the zinc-bromine battery. As a result, the life of non-flowing zinc-bromine batteries at this stage is generally not high. The maximum capacity of traditional neutral zinc-bromine batteries is generally 1.5mAh / cm 2 In addition, its capacity generally begins to decline rapidly after 100 cycles, and its general life span does not exceed 200 cycles. Summary of the invention

[0004] In order to solve the above technical bottlenecks, the present invention proposes a zinc-bromine battery based on murexide-modified electrolyte and a preparation method thereof. The present invention mainly uses murexide-modified zinc-bromine electrolyte, reduces the activity of water molecules by using high concentration of zinc bromide (5 mol / L), adds potassium hydroxide to adjust the pH value of the electrolyte, and finally adds potassium bromate and murexide to modify the electrolyte, thereby improving the discharge voltage and discharge capacity of the battery, and slowing down the corrosion and zinc deposition of the zinc electrode to extend the battery life. The present invention adopts a mixed aqueous solution electrolyte of ZnBr2+KOH+KBrO3+murexide, graphite paper as the cathode, and relatively stable zinc metal as the anode material of the battery. Thanks to the combined action of bromide ions and zinc ions, the discharge platform of the battery can reach 1.55V-1.65V. At 30mA / cm 2 The activation was performed about 25 times at a current density of . The battery voltage was increased to 1.65V, and the discharge capacity was improved. The battery life can reach 2000 cycles. Therefore, the new zinc-bromine battery proposed by the present invention not only has improved performances such as voltage, capacity and life, but also has a wide range of raw materials and low prices, and can replace lithium-ion batteries to meet today's development needs.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A zinc-bromine battery based on murexide modified electrolyte, wherein the zinc-bromine battery has graphite paper as a positive electrode, zinc foil as a negative electrode, and the electrolyte is a mixed aqueous solution of zinc bromide, potassium hydroxide, potassium bromate and murexide. In the mixed aqueous solution, the concentration of zinc bromide is 4-6 mol / L, the concentration of potassium hydroxide is 80-120 g / L, the concentration of potassium bromate is 10-75 g / L, and the concentration of murexide is 10 g / L (supersaturated).

[0007] Furthermore, the mixed aqueous solution preferably contains 5 mol / L zinc bromide, 100 g / L potassium hydroxide, 50 g / L potassium bromate, and 10 g / L murexamium.

[0008] A method for preparing a zinc-bromine battery based on a murexate-modified electrolyte comprises the following steps:

[0009] (1) The zinc sheet was sanded to remove the surface oxide, and then the graphite paper and the zinc sheet were washed with ethanol and distilled water respectively, and then vacuum dried.

[0010] (2) Preparing a mixed aqueous solution as an electrolyte

[0011] First, a zinc bromide aqueous solution with a concentration of 5 mol / L is prepared as an aqueous electrolyte, and a high concentration of zinc bromide is used to reduce the activity of water molecules; potassium hydroxide is then added to the zinc bromide aqueous solution to adjust the pH value to neutral; potassium bromate and ammonium murexate are added to the above solution to modify the electrolyte, and a mixed aqueous solution is obtained as the final electrolyte, which perfectly realizes a zinc-bromine battery system with high discharge and high capacity.

[0012] (3) Use graphite paper as the positive electrode and zinc sheet as the negative electrode to assemble into a soft-pack battery or a box-type membrane-free and flow-free battery.

[0013] (4) The battery is charged and discharged for activation and optimal performance.

[0014] Furthermore, the current density used in the activation process is 10 mA / cm 2 ~50mA / cm 2 , preferably 30mA / cm 2 The activation charge and discharge cycle number is about 25 cycles.

[0015] The reaction mechanism of the present invention is as follows:

[0016] In the zinc bromide electrolyte system, graphite paper is used as the positive electrode and zinc sheet is used as the negative electrode. During the discharge process of the battery, the zinc valence changes from 0 to +2, and the polybrominated ions on the positive electrode undergo a reduction reaction with the ammonium murexate complex, the valence state decreases, and the polybrominated compounds are converted into bromide ions to continue to complex with ammonium murexate. During the charging process, the positive electrode bromide ion complex is converted into a polybrominated ion complex to raise the valence state again, or a disproportionation reaction occurs to convert it into a bromate ion or a hypobromite ion, and the negative electrode is reduced to zinc. The reaction equation of the battery is as follows:

[0017] positive electrode:

[0018] negative electrode:

[0019] The beneficial effects of the present invention are:

[0020] (1) The present invention proposes a neutral zinc-bromine electrolyte and applies it as an electrolyte for zinc-bromine batteries. The assembled soft-pack batteries and box-type membrane-free and flow-free batteries both exhibit good electrochemical performance. The pH value of the electrolyte is adjusted to neutral, and the bromate ions in potassium bromate are used to induce a disproportionation reaction. The bromine is further fixed by using ammonium murexate to form a complex with polybromine ions, thereby reducing the generation of bromine gas and increasing the battery life.

[0021] (2) The present invention not only makes the zinc-bromine electrolyte close to neutrality and improves safety, but also takes advantage of the low price and stable performance of graphite paper and zinc sheets. It is an environmentally friendly, high-performance new zinc-bromine battery, and therefore has great application value and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The working principle and practical application diagram of the zinc-bromine battery obtained in Example 3. Figure 1 (a) is a working principle diagram of the zinc-bromine battery; Figure 1 (b) is the actual assembly diagram of the battery soft pack.

[0023] Figure 2 This is the charge and discharge curve diagram of the zinc-bromine battery obtained in Example 3. Figure 2 (a) is a comparison chart of battery capacities corresponding to electrolytes containing different substances; Figure 2 (b) is a battery charge and discharge curve corresponding to electrolytes containing different substances; Figure 2 (c) is a cyclic voltammogram of the zinc-bromine battery; Figure 2 (d) Capacity comparison chart containing different amounts of potassium bromate.

[0024] Figure 3 This is the test spectrum of the zinc-bromine battery under charge and discharge conditions obtained in Example 3. Figure 3 (a) XRD pattern of electrolyte compared with standard XRD patterns of urea-based substances and bromine. (b) XRD patterns of positive electrodes corresponding to different electrolytes. (c) XRD patterns of positive electrodes during charge and discharge.

[0025] Figure 4 (a) is the XPS image of the charged electrode. (b) is the XPS image of the discharged electrode. (c) is the Raman image of the charged electrode at different cycles. (d) is the Raman image of the charged and discharged electrodes. DETAILED DESCRIPTION

[0026] The present invention is further described below.

[0027] Comparative Example 1

[0028] The zinc sheet was sanded to remove the surface oxide, and then the graphite paper and zinc sheet were washed with ethanol and distilled water for 5 minutes respectively and dried in a vacuum for 30 minutes. The graphite paper and zinc sheet were cut into 2.5cm*2.5cm sheets as the positive and negative electrodes of the battery.

[0029] First, take 10 ml of deionized water to the sesame cake, weigh 1 g of potassium hydroxide on an electronic scale and add it to the deionized water, then weigh 5 mol / L of zinc bromide and add it, stir for 20 minutes to obtain an electrolyte. Use the treated zinc sheet and graphite paper to assemble a soft package battery or a box-mounted membrane-free and flow-free battery. In the electrolyte of this embodiment, the concentration of zinc bromide is 5 mol / L, and the concentration of potassium hydroxide is 100 g / L.

[0030] The battery was charged and discharged for activation, where the current density used in the activation process was 30 mA / cm 2 The number of activation charge and discharge cycles is 25 cycles.

[0031] The maximum discharge capacity is 1.5 mAh / cm 2 , but the capacity begins to decrease rapidly after 100 cycles.

[0032] Comparative Example 2

[0033] The zinc sheet was sanded to remove the surface oxide, and then the graphite paper and zinc sheet were washed with ethanol and distilled water for 5 minutes respectively and dried in a vacuum for 30 minutes. The graphite paper and zinc sheet were cut into 2.5cm*2.5cm sheets as the positive and negative electrodes of the battery.

[0034] First, take 10 ml of deionized water to the biscuit, weigh 1 g of potassium hydroxide on an electronic scale and add it to the deionized water, then weigh 0.1 g of murexide and add it to the beaker, stir for 10 minutes, then weigh 5 mol / L of zinc bromide and add it, continue stirring for 20 minutes to obtain an electrolyte. Use the treated zinc sheet and graphite paper to assemble a soft-package battery or a boxed membrane-free and flow-free battery. In the electrolyte of this embodiment, the concentration of zinc bromide is 5 mol / L, the concentration of potassium hydroxide is 100 g / L, and the concentration of murexide is 10 g / L.

[0035] The battery was charged and discharged for activation, where the current density used in the activation process was 30 mA / cm 2 The number of activation charge and discharge cycles is 25 cycles.

[0036] The battery open circuit voltage is 1.65V, and the discharge capacity reaches its maximum at the initial stage, which is about 1.27mAh / cm 2 , after which the capacity remains stable, but when the cycle reaches about 700 times, the capacity begins to decrease rapidly.

[0037] Comparative Example 3

[0038] The zinc sheet was sanded to remove the surface oxide, and then the graphite paper and zinc sheet were washed with ethanol and distilled water for 5 minutes respectively and dried in a vacuum for 30 minutes. The graphite paper and zinc sheet were cut into 2.5cm*2.5cm sheets as the positive and negative electrodes of the battery.

[0039] First, take 10 ml of deionized water to the sesame cake, weigh 1 g of potassium hydroxide on an electronic scale and add it to the deionized water, then weigh 0.5 g of potassium bromate and add it to the beaker, stir for 10 minutes, then weigh 5 mol / L of zinc bromide and add it, continue stirring for 20 minutes to obtain an electrolyte. Use the treated zinc sheet and graphite paper to assemble a soft-package battery or a box-mounted membrane-free and flow-free battery. In the electrolyte of this embodiment, the concentration of zinc bromide is 5 mol / L, the concentration of potassium hydroxide is 100 g / L, and the concentration of potassium bromate is 50 g / L.

[0040] The battery was charged and discharged for activation, where the current density used in the activation process was 30 mA / cm 2 The number of activation charge and discharge cycles is 25 cycles.

[0041] The battery open circuit voltage is 1.6V, and the discharge capacity reaches its maximum after about 5 times, which is about 2.12mAh / cm 2 , after which the capacity remains stable, but begins to decline rapidly around 700 cycles.

[0042] Example 1

[0043] The zinc sheet was sanded to remove the surface oxide, and then the graphite paper and zinc sheet were washed with ethanol and distilled water for 5 minutes respectively and dried in a vacuum for 30 minutes. The graphite paper and zinc sheet were cut into 2.5cm*2.5cm sheets as the positive and negative electrodes of the battery.

[0044] First, take 10ml of deionized water to the biscuit, weigh 1g of potassium hydroxide on an electronic scale and add it to the deionized water, then weigh 0.1g of murexate and 0.5g of potassium bromate and add them to a beaker, stir for 10 minutes, then weigh 5mol / L of zinc bromide and add it, continue stirring for 20 minutes to obtain an electrolyte. Use the treated zinc sheet and graphite paper to assemble a soft-package battery or a boxed membrane-free and flow-free battery. In the electrolyte of this embodiment, the concentration of zinc bromide is 5mol / L, the concentration of potassium hydroxide is 100g / L, the concentration of potassium bromate is 50g / L, and the concentration of murexate is 10g / L.

[0045] The battery was charged and discharged for activation, where the current density used in the activation process was 30 mA / cm 2 The number of activation charge and discharge cycles is 25 cycles.

[0046] The battery open circuit voltage is 1.65V, and the discharge capacity reaches its maximum after about 20 cycles, which is about 2.31mAh / cm 2 , and the capacity will remain stable thereafter. When the capacity decays to 1.2 mAh / cm 2 The battery cycle life has reached more than 2000 cycles, and the capacity has not decreased rapidly.

[0047] Example 2

[0048] The zinc sheet was sanded to remove the surface oxide, and then the graphite paper and zinc sheet were washed with ethanol and distilled water for 5 minutes respectively and dried in a vacuum for 30 minutes. The graphite paper and zinc sheet were cut into 2.5cm*2.5cm sheets as the positive and negative electrodes of the battery.

[0049] First, take 10 ml of deionized water to the biscuit, weigh 0.8 g of potassium hydroxide on an electronic scale and add it to the deionized water, then weigh 0.1 g of murexate and 0.1 g of potassium bromate and add them to a beaker, stir for 10 minutes, then weigh 4 mol / L of zinc bromide and add it, continue stirring for 20 minutes to obtain an electrolyte. Use the treated zinc sheet and graphite paper to assemble a soft-package battery or a boxed membrane-free and flow-free battery. In the electrolyte of this embodiment, the concentration of zinc bromide is 4 mol / L, the concentration of potassium hydroxide is 80 g / L, the concentration of potassium bromate is 10 g / L, and the concentration of murexate is 10 g / L.

[0050] The battery was charged and discharged for activation, where the current density used in the activation process was 10 mA / cm 2 The number of activation charge and discharge cycles is 25 cycles.

[0051] The battery open circuit voltage is 1.65V, and the discharge capacity reaches its maximum after about 20 cycles, which is about 2.03mAh / cm 2 , and the capacity will remain stable thereafter. When the capacity decays to 1.2 mAh / cm 2 The battery cycle life has reached more than 1500 cycles, and the capacity has not decreased rapidly.

[0052] Example 3

[0053] The zinc sheet was sanded to remove the surface oxide, and then the graphite paper and zinc sheet were washed with ethanol and distilled water for 5 minutes respectively and dried in a vacuum for 30 minutes. The graphite paper and zinc sheet were cut into 2.5cm*2.5cm sheets as the positive and negative electrodes of the battery.

[0054] First, take 10 ml of deionized water to the biscuit, weigh 1.2 g of potassium hydroxide on an electronic scale and add it to the deionized water, then weigh 0.1 g of murexate and 0.75 g of potassium bromate and add them to a beaker, stir for 10 minutes, then weigh 6 mol / L of zinc bromide and add it, continue stirring for 20 minutes to obtain an electrolyte. Use the treated zinc sheet and graphite paper to assemble a soft-package battery or a boxed membrane-free and flow-free battery. In the electrolyte of this embodiment, the concentration of zinc bromide is 6 mol / L, the concentration of potassium hydroxide is 120 g / L, the concentration of potassium bromate is 75 g / L, and the concentration of murexate is 10 g / L.

[0055] The battery was charged and discharged for activation, where the current density used in the activation process was 50 mA / cm 2 The number of activation charge and discharge cycles is 25 cycles.

[0056] The battery open circuit voltage is 1.65V, and the discharge capacity reaches its maximum after about 20 cycles, which is about 2.23mAh / cm 2 , and the capacity will remain stable thereafter. When the capacity decays to 1.2 mAh / cm 2 The battery cycle life has reached more than 1800 cycles, and the capacity has not decreased rapidly.

[0057] Figure 1 The working principle and practical application diagram of the zinc-bromine battery. During the discharge process of the battery, the zinc valence changes from 0 to +2, and the polybromine ions on the positive electrode react with the ammonium murexate complex to reduce the valence state. During the charging process, the polybromine ion complex at the positive electrode increases the valence state again, and the negative electrode is reduced to zinc. The reaction equation of the battery is as follows:

[0058] positive electrode:

[0059] negative electrode:

[0060] Figure 2 is the charge and discharge curve of zinc-bromine battery. Figure 2 (a) It can be seen that the combined effect of ammonium murexate and potassium bromate can improve the capacity and life of the battery, reaching a maximum capacity of 2.31 mAh / cm 2 , the service life can reach 2000 cycles. Figure 2 In (b), ammonium murexate improves the discharge platform of the battery to around 1.65V. Figure 2 (c) can also confirm the discharge platform. Figure 2 (d) It can be seen that the amount of potassium bromate added has a certain effect on the capacity improvement of the entire battery. In addition, ammonium murexate has a certain positive effect on inhibiting the generation of bromine gas and inhibiting the corrosion of the zinc electrode.

[0061] Figure 3 This is the XRD test spectrum of zinc-bromine battery under charging and discharging conditions. Figure 3 (a) is to directly test the dried electrolyte and compare the standard XRD patterns of urea-based substances and bromine to prove the presence of bromine and urea-based substances in the electrolyte. Figure 3(b) shows the XRD images of the positive electrode after 200 charge and discharge cycles using electrolytes containing different components. An obvious peak appears near 2θ=27°, which is caused by bromine-based substances. The addition of ammonium murexide electrolyte leads to a decrease in impurity peaks in the XRD image, indicating its fixing effect on the substances in the electrolyte. In addition, the electrolyte containing potassium bromate exhibits peaks at 2θ=22° and 33°. However, the positive electrode image corresponding to the electrolyte without the addition of ammonium murexide is very chaotic. Figure 3 In (c), the XRD patterns before and after charging are compared. It can be clearly seen that the peak at 2θ = 27° disappears after discharge, indicating that the bromine or polybromine ions attached to the positive electrode have been converted into bromine and re-entered the electrolyte. Therefore, the peak corresponding to the bromine-based species in the positive electrode disappears.

[0062] Compare Figure 4 (a) and (b), the Br 3d XPS spectra of the charged electrode can be fitted with three peaks at 71.6 eV, 70.1 eV, and 68.6 eV, corresponding to Br5 - Br3 - and Br - However, after discharge, Br3 - and Br5 - The intensity of the peak is significantly reduced, and Br- dominates the discharge electrode. Figure 4 In (c), the electrode shows a Raman spectrum of 200 cm -1 Up to 300cm -1 Raman band, which is Br n - Another proof of existence. 1773cm -1 and 2772cm -1 The Raman peaks at are CN and CO bonds, which gradually decrease during the cycle. Murexide may decompose with the charge-discharge cycle, resulting in a decrease in its content. However, the peaks corresponding to bromine compounds change relatively little, indicating that they are restricted throughout the charge and discharge process. Figure 4 In (d), after discharge, the three original Raman characteristic peaks on the electrode disappear, indicating that the complex formed by bromine and murexate re-enters the electrolyte during discharge. It confirms that polybromine has been successfully confined, ensuring that the redox reaction of bromide / polybrominated species in the battery is highly reversible.

[0063] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A zinc-bromine battery based on murexide-modified electrolyte, characterized in that: The zinc-bromine battery uses graphite paper as the positive electrode, zinc foil as the negative electrode, and the electrolyte is a mixed aqueous solution of zinc bromide, potassium hydroxide, potassium bromate and ammonium murexate.

2. A zinc-bromine battery based on murexide modified electrolyte according to claim 1, characterized in that: In the mixed aqueous solution, the concentration of zinc bromide is 4-6 mol / L, the concentration of potassium hydroxide is 80-120 g / L, the concentration of potassium bromate is 10-75 g / L, and the concentration of murexide is supersaturated.

3. A zinc-bromine battery based on murexide modified electrolyte according to claim 1, characterized in that: In the mixed aqueous solution, preferably: the concentration of zinc bromide is 5 mol / L, the concentration of potassium hydroxide is 100 g / L, the concentration of potassium bromate is 50 g / L, and the concentration of murexide is 10 g / L.

4. A method for preparing a zinc-bromine battery based on murexide-modified electrolyte according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) washing the graphite paper and the polished zinc sheet with ethanol and distilled water respectively, and then vacuum drying; (2) preparing a mixed aqueous solution as an electrolyte; First, a zinc bromide aqueous solution is prepared, and potassium hydroxide is added to the zinc bromide aqueous solution to adjust the pH value to be neutral; potassium bromate and ammonium murexate are added to the above solution to modify the electrolyte, and a mixed aqueous solution is obtained as an electrolyte; (3) Use graphite paper as the positive electrode and zinc sheet as the negative electrode to assemble into a soft pack battery or a box-type membrane-free and flow-free battery; (4) The battery is charged and discharged for activation and optimal performance.

5. The method for preparing a zinc-bromine battery based on murexide-modified electrolyte according to claim 4, characterized in that: The current density used in the activation process is 10 mA / cm 2 ~50mA / cm 2 .

6. The method for preparing a zinc-bromine battery based on murexide modified electrolyte according to claim 4, characterized in that: The current density used in the activation process is preferably 30 mA / cm 2 .